A simple dressing for hypospadias surgery in children - Méndez-Gallart, Roberto; García-Palacios, Maria; Rodríguez-Barca, Pablo; Estevez-Martinez, Elina; Lema-Carril, Ana; Bautista-Casasnovas, Adolfo (Canadian Urological Association Journal, 2017)
One of the most controversial aspects of hypospadias surgery is the election of an appropriate wound dressing. In fact, there may be as many different types of dressing as there are types of surgical repair. Here, we describe a new, simple method for hypospadias dressing in children that minimizes painful removal.